Spy x family / Volume 3 - Endo, Tatsuya; Loe, Casey; Mapa, Rina (San Francisco, CA : VIZ Media, LLC, 2020)
When Master Spy Twilight finds himself tasked with playing the part of a family man to infiltrate a prestigious school, he almost ruins the case when he has an outburst in the middle of the admissions interview.
-- Volume Two: Mission Start -- Volume Four: World Peace Depends on the Forgers! -- Volume six: Mission 31
Pages numbered from right to left.
Chiefly illustrations.
Keywords: Spies -- Comic books, strips, etc. -- Juvenile fiction; Psychic ability -- Comic books, strips, etc. -- Juvenile fiction; Marriage -- Comic books, strips, etc. -- Juvenile fiction; Families -- Comic books, strips, etc. -- Juvenile fiction; Spies; Psychic ability; Marriage; Comic books, strips, etc; Marriage; Espions -- Romans, nouvelles, etc. pour la jeunesse; Romans, nouvelles, etc. pour la jeunesse; Mariage -- Romans, nouvelles, etc. pour la jeunesse; Familles -- Romans, nouvelles, etc. pour la jeunesse; Espions; Mariage; Comic books, strips, etc; Families; Marriage; Psychic ability; Spies; Humorous comics; Domestic comics; Action and adventure comics; Graphic novels; Graphic novels